Comparison of Gene Expression Between Pediatric and Adult Gastric Mucosa with Helicobacter pylori Infection. Issue 2 (3rd July 2015) - Obayashi, Naho; Ohtsuka, Yoshikazu; Hosoi, Kenji; Ikuse, Tamaki; Jimbo, Keisuke; Aoyagi, Yo; Fujii, Tohru; Kudo, Takahiro; Asaoka, Daisuke; Hojo, Mariko; Nagahara, Akihito; Watanabe, Sumio; et al.
Abstract: Background: Although Helicobacter pylori infection among adults is a major risk factor for the development of gastric cancer and initial infection with H. pylori may occur before 5 years of age, the direct effects of H. pylori infection since childhood on gastric mucosa are unknown. The aim of this study was to evaluate gene expression in the H. pylori ‐infected gastric mucosa of children. Methods: Gastric mucosal samples were obtained from 24 patients (12 adults and 12 children) who had undergone endoscopic evaluation of chronic abdominal complaints and were examined by the adult and pediatric gastroenterologists at Juntendo University Hospital. Six adult and pediatric patients with and six without H. pylori infection were enrolled. Their gastric mucosal samples obtained from the antrum and corpus were used for microarray, real‐time polymerase chain reaction, and immunohistochemical analyses to examine the expression of inflammatory carcinogenic molecules. Results: The expression of inflammatory molecules was upregulated in the H. pylori ‐infected gastric mucosa from both adults and children. The expression of olfactomedin‐4 was only upregulated in adult patients, while that of pim‐2, regenerating islet‐derived 3 alpha, lipocalin‐2, and C‐X‐C motif chemokine ligand 13 was equally upregulated in the infected gastric mucosa of both adults and children. Conclusions: Because several carcinogenic molecules are upregulated in H. pylori ‐infected gastric mucosa even in children, early eradication therapy from childhood may be beneficial to decrease the incidence of gastric cancer. Although increased expression of olfactomedin‐4 can be important in suppressing gastric cancer in adults, the increase was not detected in children.